A Power Balanced Dual-Wavelength Nd:GdVO4 Laser With 0.6 THz Frequency Separation - Yuting Zhang; Miao Hu; Mengmeng Xu; Hengfeng Yan; Chong Liu; Long Chen; Haozhen Li; Meihua Bi; Xuefang Zhou (IEEE Photonics Journal, 2022)
A power balanced dual-wavelength laser (DWL) based on the Nd:GdVO4 crystal is presented. The orthogonally polarized gain spectral evolution of the Nd:GdVO4 crystal versus the temperature is studied, and the power balancing conditions of the DWLs are theoretically analyzed firstly. In the experiments, by using two output couplers and a temperature controller, the power balanced Nd:GdVO4 DWL signals at 1063 nm (π) and 1065 nm (σ) are obtained with the crystal heat sink temperature (Tc) from 20 °C to 40 °C. The experimental results show, with the pump power at 9.3 W and Tc at 25 °C, the DWL signal of the balanced power at 0.78 W for each wavelength and the frequency separation at 0.62 THz is realized. The beam quality M2 of the π- and σ-polarized DWL signals are measured between 2.1 to 2.4.